Sobre limites e fronteiras: a reprodutibilidade do estoque territorial para os fins da acumulação capitalista - César Ricardo Simoni Santos (Confins)
The words “frontier” and “limit” are often used as synonyms, despite of the semantic reduction implied by this identification. But it is easy to see that the former is more often associated to spatial phenomena, while the latter seems to be closer to the idea of the end or exhaustion of nature. One can, nevertheless, think of a relation between them. On the economic level, the limits of capitalist reproducibility go on a par with the situation of this economic system’s own frontiers. Capitalist spatial dynamics is conceived to continually broaden its own limits, internal and external alike. The lack of alternatives for the lucrative investment accompanies the saturation of spaces for investment. Under these conditions, having reached the provisory limits of reproduction, new frontiers must be opened. The scarcity of unsaturated territorial reserves of a non-capitalistic kind over which to advance forces new investments to struggle over already occupied territory. In this scenario, new internal frontiers must be opened, and capital expansion must operate over spaces already altered and occupied by elements and processes typical of capitalistic reproduction. Thus capitalist expansion must draw on a stock of devalued assets left over as the outcome of crises or of the destruction of capital imposed by the search for new means of valorization. Thus, it seems that capital reproduction does not presuppose non-capitalistic territories or “external markets”, as suggested by Rosa Luxemburg. By forcing bankruptcy and devaluation processes on part of the active capital, some capitalists manage to recreate investment conditions inside the same inhabited and exploited space, starting a new accumulation cycle.